The role of skill acquisition in coach and athlete development in Paralympic sport - Pinder, R. A.; Powell, D.; Hadlow, S.; Askew, G.; Oudejans, R. R. D. (Talent development in Paralympic sport: Researcher and practitioner perspectives, 2022)
Practical and theoretical frameworks centred around skill acquisition (SA) aim to provide opportunities and techniques to enhance athletes` learning. Recent moves to embed SA practitioners in daily performance environments allows for insight into current coaching practices, and a means to enhance talent development pathways. While calls for more embedded coach support are not new, Para sport contexts may in fact be frontrunners in translation of knowledge for coach and athlete development. In this chapter, we highlight some of the ways applied SA support and research programs can achieve this in Para sport, using case-study insights from Great Britain and Australia. The examples provided highlight the importance of the coach-athlete-practitioner relationship, suggest that big shifts in thinking can occur over a relatively short period of time, and provide opportunities to reduce some of the barriers associated with coach and athlete development in high-performance Para sport environments.